The western confluence : a guide to governing natural resources - McKinney, Matthew (Island Press, 2004)
Annotation Traces the principles of natural resource governance across the history of western settlement and reveals how they have met at the beginning of the twenty-first century to create a turbid, often contentious confluence of laws, regulations, and policies. Offers practical suggestions for resolving current and future disputes.